Photosynthetic responses of 'Neosiphonia sp. epiphyte-infected' and healthy Kappaphycus alvarezii (Rhodophyta) to irradiance, salinity and ph variations - Borlongan, Iris Ann G. (Miag-ao, Iloilo University of the Philippines in the Visayas, 2014)
The study aimed to examine photosynthetic performances of Neosiphonia sp. epiphyte-infected (INF) and healthy (HEA) K. aalvarezii in response to irradiance, salinity and pH variations using photosynthesis-irradiance (P-I) curves. Specifically, it aimed to measure and compare (a) photosynthetic rates, and (b) photosynthetic pigments of both Neosiphonia-infected and healthy K. alvarezii as subjected to different combinations of irradiance, salinity (20, 25, 30, 35 and 40%) and pH (6, 7, 8 and 9). Results of this study may be useful for the improvement of farming and management protocols of these hig-valued seaweed cultivars. Measurements of algal photosynthetic rates, as express in terms of amount of oxygen production per fresh weight biomass per unit (mg O2 g-1 FW h-1), were carried out using the light-dark bottle technique. Results revealed Neosiphonia-infected K. alarezii having lower photosynthetic rates than the healthy ones at all irradiance levels. INF K. alvarezzii attained light-saturated photosynthesis rates (Pmax) at irradiances ranging from 673 to 695 umol photons m-2 s-1, which are higher as compared to HEA K. alvrezii (290 to 460 umol photons m-2 s-1. Similarities (p>0.05) in Pmax and significant differences (p<0.05) in initial slope of curve (a) between INF and HEA K. alvarezii suggest hat both samples are adapted to similar light conditions : and differs only on photosynthetic efficiency Low values for Pmax and high initial saturation irradiances (lk) of epiphyte-infected seaweeds resulted to their low photosythetic efficiency (a=0.002-0.010), indicating reduced activity. Such decline in photosyntheic efficiency is attrbuted to the epiphyte, as Nesiphonia sp. covered almost the entire surface of K. alvarezii, thereby limiting its metabolic function. An increase in chlrophyll a and phycobilin contents was also observed in Neosiphonia-infected samples, suggesting an acclimation response to low-irradiance conditions, since both algae compete for the same photosynthetically active radiation (PAR). The parameters derived from the P-I relationship indicated the broad irradiance variations in both INF and HEA K. alvarezii, with no photodamage at the highest irradiance level of 850 umol photons m-2 s-1. K. alvarezii photosynthesized efectively at 290 to 460 umol protons m-2 s-1, which matchcd with the range of irradiances at 50-100 cm culture depths, where k. alvarezii obtained intermediate growth rates and minimal Neosiphonia infection. Both INF and HEA k alvarezii also exhibited broad photosynthetic tolerance to short-term salinity-pH fluctuations, with no significant differences (p>0.05) in their P-I parameter values and pigment contents. K alvarezzi had a euryhaline photosynthetic response, with optimum salinity of 35%. photosynthetic affinity for acidic seawater conditins.
Thesis (M. S. Biology) -- Miagao, Iloilo : U. P. in the Visayas, February 2014.